Analisis Kemajuan Penambangan Batubara Menggunakan Surpac dan Prismoidal Di Kalimantan Timur - Arsdin, Dian Dwi Apriliyani; Harwan, Harwan (Jurnal of Mining Insight, 2024)
In general, coal mining in indonesia uses the open pit mining method, one of the critical success of this mining method is the stripping of over burden which is above the coal seam itself. Thus the purpose of this research is to calculate and analyze the progress of mining on the activities of over burden stripping. In this study measurement is done through cress, toe, and spot on coal mining using total station, from the measurement results are processed and then compared the volume of the stripped over burden by using surpac and prismoidal. The volume result of the mined over burden by surpac during the first week is 10,643 m3, second week 54,556 m3, and on the third week 63,596 m3, while the calculation result by prismoidal during the first week is 11,66 m3, second week 53,99 m3, and on the third week 64,64 m3. So from the comparison mining volume of stripping over burden between surpac and prismoidal on the first week 1.02, second week 0.56, and third week 1.05. Based on the comparison it is concluded that the surpac and prismoidal have calculation results tend to be similar in comparison.